1998
DOI: 10.1177/0887302x9801600204
|View full text |Cite
|
Sign up to set email alerts
|

Building a Financially Meaningful Language of Merchandise Assortments

Abstract: The objectives of this exploratory study included identifying functional relationships between the nature of assortments and potential financial performance and proposing financially relevant definitions and related language for assortment planning. The research method was computer simulation of the merchandising process. Results indicated that more diverse assortments are less financially productive than focused assortments. A definition of assortment diversity was developed and an Assortment Diversity Index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…14 From the retailer perspective, the desired merchandise mix must satisfy preferences of the target market while also being financially productive for the retailer. 15 Souvenir merchandise can be classified into five broad categories: 16 pictorial image souvenirs (postcards or booklets), piece-of-therock souvenirs (items found in nature), symbolic shorthand souvenirs (items that evoke a message about the place they came from), markers (items inscribed with the location from which they came) and local product souvenirs (items indigenous to the area). Representative items from each of these categories are sold across the American south-west including jewellery, pottery, clothing, weavings, toys, food and other products.…”
Section: Dimensions Of Souvenir Purchase Behaviour Souvenir Productsmentioning
confidence: 99%
“…14 From the retailer perspective, the desired merchandise mix must satisfy preferences of the target market while also being financially productive for the retailer. 15 Souvenir merchandise can be classified into five broad categories: 16 pictorial image souvenirs (postcards or booklets), piece-of-therock souvenirs (items found in nature), symbolic shorthand souvenirs (items that evoke a message about the place they came from), markers (items inscribed with the location from which they came) and local product souvenirs (items indigenous to the area). Representative items from each of these categories are sold across the American south-west including jewellery, pottery, clothing, weavings, toys, food and other products.…”
Section: Dimensions Of Souvenir Purchase Behaviour Souvenir Productsmentioning
confidence: 99%
“…This customer scenario poses a challenge to merchandisers to have a particular combination of style, size, and color in stock when the customer wants it. However, offering diverse merchandise assortments has resulted in the profit-draining problems of high rates of unsold merchandise and markdowns (Abernathy et al, 1999;Rifkin, 1994;Rupe & Kunz, 1998). Inventory and markdown costs are often 20% to 30% of the cost of a garment (Blair, 1999).…”
mentioning
confidence: 99%
“…From a tourist perspective, the right souvenir assortment offered by retailers must be tangible articles that evolve the intangible memories of their experiences (Littrell et al, 1994). Taken from the retailer perspective, the desired merchandise mix must satisfy preferences of the target market and be financially productive (Rupe & Kunz, 1998). Gordon (1986) suggested that local products serve as one type of souvenir.…”
Section: Souvenir Merchandise Assortmentmentioning
confidence: 99%